A new species of Chamaecrista sect. Absus (Leguminosae, Caesalpinioideae) from Minas Gerais, Brazil, with Notes on Leaf Anatomy - Couto Zeferino, Laís; Lewis, Gwilym Peter; de Vargas, Wanderleia; Cândido, Elisa S.; Vatanparast, Mohammad; Da Silva, Marcos José; Murashima, Pedro Hiroshi Pereira; Fortuna-Perez, Ana Paula (Phytotaxa, 2022)
A new species of Chamaecrista was found in the Serra do Espinhaço region in the state of Minas Gerais, Brazil, during an expedition to study the taxonomy of this genus. Chamaecrista sempreviva Fort.-Perez & L.C. Zeferino sp. nov. is herein described, illustrated, and assigned to Chamaecrista sect. Absus. Comments about the ecology, distribution, preliminary conservation status as well as its morphological relationships and flowering and fruiting season of the new species, are provided. Additionally, a secretory structure survey of the leaflets of the new species and its related congeners is presented. All species studied share the presence of secretory and mucilaginous idioblasts in their leaflets, but the position of these cells types serves to differentiate them.